Potential issues in novel computational research: artificial immune systems - Iqbal, Anjum; Maarof, Mohd. Aizaini (2003)
Recent trends in computational research show the significance of computation-based biological research, for example, bioinformatics and system biology, and biologically inspired computational research, which includes genetic algorithms, artificial neural networks, and evolutionary programming. Artificial immune systems (AIS) is a novel computing paradigm inspired from the human immune system (HIS). The dramatic features of HIS like distributability, uniqueness, adaptability, mobility, imperfect-detection, and anomaly-detection, have grabbed the attention of computational researchers for adopting HIS principles to design AIS that are robust, scalable, highly flexible, resilient to sub-versioning, and degrade gracefully. Designers of AIS make use of their creative abilities for designing computational systems by extracting corresponding metaphors from HIS. AIS is growing as a core paradigm for a wide application area including: intrusion detection, data analysis, pattern recognition, optimization, robotics, distributed control, and bioinformatics etc. The field of AIS, being in its infancy, bears enormous research potential. This work aims to throw light on some prospective research issues in the field. The effort is based on (1) latest research references and (2) our experience for pioneering AIS based research infrastructure in the Universiti Teknologi Malaysia (UTM). It may help new researchers to jump start AIS research and save their precious time.